Electrical resistivity measurements of down scaled homogenous rocks for network model validation (2011)
Knowledge of electrical resistivity for reservoir rocks is crucial for a number reservoir engineering tasks such as the determination of oil-in place and the calibration of resistivity logs. Those properties can now be predicted by numerical calculations directly on micro -CT images taken from rock fragments typically having a bulk volume of 100mm3. The experimental data used to validate those predictions are obtained on conventional cores having bulk volumes of the order of 10.000mm3. A better validation of micro-CT technique would be to use the same core size for both imaging and flow experiment. Experimental data for electrical resistivity measurements using micro pore membrane and centrifuge desaturation techniques are presented for cores having bulk volumes from 10.000mm3 down to 100mm3. Both 2 - and 4 - electrode techniques w ere applied to measure the resistivity index. Simple fluids like brine and air were used for clear wettability. Homogeneous sandstone cores (Berea and Bentheim) and a carbonate core (Mount Gambier) were used in the experiments. The results demonstrate that reliable experimental data of resistivity index can be obtained f o r the small cores of homogeneous porous rocks at sensitized frequency. Such data are of immense interest f o r validating the predictive value of network models based on micro -CT imaging of rock fragments with bulk volumes as small as 100mm3